2016
DOI: 10.1120/jacmp.v17i4.6194
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric accuracy of the cone‐beam CT‐based treatment planning of the Vero system: a phantom study

Abstract: We report an investigation on the accuracy of dose calculation based on the cone‐beam computed tomography (CBCT) images of the nonbowtie filter kV imaging system of the Vero linear accelerator. Different sets of materials and tube voltages were employed to generate the Hounsfield unit lookup tables (HLUTs) for both CBCT and fan‐beam CT (FBCT) systems. The HLUTs were then implemented for the dose calculation in a treatment planning system (TPS). Dosimetric evaluation was carried out on an in‐house‐developed cub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Commercial phantoms are now available that provide additional material perpendicular to the CT slices (depth), although a number of authors [33,43,54,55] have reported mimicked this by adding additional material either side of the standard electron density phantoms described above. Differences from the reference dose of less than 0.8% were reported using the Gammex RMI467 phantom [34,46,56] and generally less than 2.0% using CIRS062M phantom when used with extra slabs of water equivalent material to increase the scatter [43,54]. Hatton et al [33] reported mean dose differences up to 22.0% from ionisation chamber measurements when applying a calibration curve from a large diameter phantom to a smaller object, and up to 12.0% when a calibration curve from a small phantom was used for a larger object.…”
Section: Cbct Calibrationmentioning
confidence: 91%
See 1 more Smart Citation
“…Commercial phantoms are now available that provide additional material perpendicular to the CT slices (depth), although a number of authors [33,43,54,55] have reported mimicked this by adding additional material either side of the standard electron density phantoms described above. Differences from the reference dose of less than 0.8% were reported using the Gammex RMI467 phantom [34,46,56] and generally less than 2.0% using CIRS062M phantom when used with extra slabs of water equivalent material to increase the scatter [43,54]. Hatton et al [33] reported mean dose differences up to 22.0% from ionisation chamber measurements when applying a calibration curve from a large diameter phantom to a smaller object, and up to 12.0% when a calibration curve from a small phantom was used for a larger object.…”
Section: Cbct Calibrationmentioning
confidence: 91%
“…Both deformable image registration [27][28][29] and artificial intelligence-based methods [16,[30][31][32] were adopted for generating vCT in dose calculation studies. Only two studies reported on the use of farmer chambers and Gafchromic films to measure the actual ground truth dose [33,34] and the measured dose was compared both with the pCT and the CBCT calculated dose.…”
Section: Reference Dosementioning
confidence: 99%
“…The evaluation is important because, CT analysis currently begins to use quantitative analysis techniques, where accuracy of HU values and its linearity are considered as main indicators [35]. In addition, the CT scanner with IR methods is sometime used in treatment planning where HU accuracy also determines the accuracy of dose planning on radiotherapy to produce better therapeutic outcomes [36]. Although there were several studies evaluating image quality and dose reduction in the IR method [19][20][21][22][23][24][25], the linearity evaluation of HU values has never been carried out.…”
Section: Discussionmentioning
confidence: 99%
“…The HU linearity evaluation is an important parameter to quantitatively investigate the image quality for maintaining the accuracy of the diagnosis process [35]. Moreover, in the treatment planning systems of radiotherapy, the HU linearity is also as an essential parameter to determine the accuracy of dose planning [36]. Therefore, this research aims to evaluate HU linearity generated by IR techniques and compared to the those acquired by FBP techniques.…”
mentioning
confidence: 99%
“…The system was used to acquire a kV/kV-OIP and a volumetric CBCT data set using a clockwise rotation (315-45°) of one kV-imager with the following parameters:~100 kV, 100 mA, 5 s; 3 mm slice thickness and 512 × 512 matrix size. The field of view (FOV) is restricted to 200 mm in diameter and 150 mm in length [27,28]. All patients were first arranged to skin markers.…”
Section: Patient Setupmentioning
confidence: 99%